Analisis Disiplin Kerja Dalam Meningkatkan Kinerja Pegawai Pada Kantor P3DW Karawang - Zulfa Fauziah; Sungkono (Jurnal Ekonomi dan Bisnis Digital, 2024)
This research aims to analyze work discipline in improving employee performance at the P3DW Karawang office. This research method is qualitative research and a descriptive approach. The data collection techniques used were interviews, documentation and observation. The results of the research are that the application of discipline at the P3DW Karawang office is still less than optimal, because there are still many employees who commit violations regarding unexplained absences, late attendance and leaving work before the appointed time. This will be a problem in an agency because it will reduce performance. With work discipline, employees are expected to be able to maintain their commitment to always work according to the regulations set by the company and to minimize violations committed, as well as having a sense of responsibility for the tasks given, of course performance will increase.